Methods may matter in injury surveillance: “how” may be more important than “what, when or why” - Tabben, Montassar; Whiteley, Rodney; Wik, Eirik; Bahr, Roald; Chamari, Karim (Biology of Sport, 2020)
To examine if and how adjustments in injury surveillance recording methodology may have influenced injury rates. Injury and exposure data were collected among professional male players from the Qatar Stars League from the 2008-2009 season to the 2017-2018 season. There have been four iterations of our data collection methods. In the first five seasons, participation in the programme was voluntary. For seasons 6-7, additional dedicated researchers were tasked with contacting the medical teams every month. At the start of season 8, an electronic recording method was instituted. In the final two seasons, injury surveillance participation was further boosted by reinforced encouragement from institutional management. Overall injury incidence increased from season 5 to season 8. Severe injuries have fallen steadily, but slightly over the ten seasons, whereas mild injuries increased dramatically from seasons 5 to 8. The current data suggest that along with the standard metrics (e.g. injury incidence, injury burden) we also need to clearly report the methods by which data were collected and verified in as much detail as possible. We suggest that sports medicine journals should adopt minimum reporting standards and perhaps checklists could be a useful step forward.